Multiscale Modeling of Heat Transfer in Graphene-Copper Nanocomposites - Goor, L.A. van; Lee, H.; Jafari, D.; Lyulin, A.V.; Wits, W.W.; Geurts, B.J. (ECCOMAS, 2025)
This study investigates the thermal properties of graphene-copper metal-matrix composites, resolving nanoscale structures through Non-Equilibrium Molecular Dynamics (NEMD) simulations and developing a continuum-upscaled model using homogenization. The continuum model is based on the NEMD findings and aims to predict the thermal properties of graphene-copper powders, which serve as feedstock material for Additive Manufacturing (AM).